Double‐blind, randomized, placebo‐controlled study of safety, tolerability, pharmacokinetics and pharmacodynamics of TAK‐683, an investigational metastin analogue in healthy men. (10th January 2013) - Scott, Graham; Ahmad, Irfan; Howard, Katy; MacLean, David; Oliva, Cristina; Warrington, Steve; Wilbraham, Darren; Worthington, Paul
<x xml:space="preserve">Abstract</x> Aims Two randomized, double‐blind, placebo‐controlled studies were performed to characterize the safety, tolerability, pharmacokinetics (PK) and pharmacodynamics (PD) of the investigational metastin analogue, TAK‐683, in healthy men. Methods We first investigated a single subcutaneous (s.c.) dose of TAK‐683 (0.01–2.0 mg) in 60 subjects (TAK‐683, n = 42; placebo, n = 18). We then assessed a single s.c. bolus of 0.03–1.0 mg TAK‐683 on day 1, followed by a 0.01–2.0 mg day−1 continuous infusion on days 2–13, to simulate a depot formulation, in 30 subjects (TAK‐683, n = 25; placebo, n = 5) for 14 days. Results TAK‐683 was well tolerated up to a dose of 2.0 mg day−1 by continuous s.c. infusion for 14 days. Adverse events were similar between TAK‐683 and placebo subjects at all dose levels. TAK‐683 plasma concentrations generally increased in proportion to dose with single and continuous dosing, with steady‐state concentrations achieved by day 2 of continuous dosing. TAK‐683 at 2.0 mg day−1 suppressed testosterone below castration level (<50 ng dl−1) in four of five subjects by day 7 of continuous dosing. Luteinizing hormone and follicle stimulating hormone concentrations were suppressed with TAK‐683 continuous dosing compared with placebo by up to 70 and 43%, respectively, but this was not consistently dose‐dependent. Conclusions In healthy men, s.c. administration of TAK‐683 was well tolerated at all dose levels. The PK profile of TAK‐683 was favourable, and TAK‐683 suppressed testosterone profoundly during continuous dosing. Further investigation of metastin analogues is warranted for the treatment of castration‐resistant prostate cancer.